Athletic ability and the anatomy of motion - Wirhed, Rolf, ....- (London : Mosby / Elsevier, 2006)
This book explains the anatomy function of different parts of the body and examines the types of movement important in sports activities. This book gives a detailed analysis of movement, general characteristics of bones, joints, and muscles, as well as guidelines for flexibility and strength training. It emphasizes important factors for maximizing performance and is a bridge between biomechanics and the practice of sport. The book's unique approach features a rigorous application of biomechanics to sport training. Mechanics are related to the use of muscles in specific sports. Coverage is both theoretical and practical, making the book useful both for academic study and as a training aid. Highly illustrated format helps readers understand key concepts and important details. Fully updated content provides the latest knowledge on the subject. New illustrations and new, engaging text layout draw the reader in and bring important concepts to life. Additional coverage has been added on several topics, including strength training.